Permasalahan korupsi di indonesia yang menjadi penyakit nasional: Gen-Z gunakan #KaburAjaDulu sebagai resistensi pasif terhadap oligarki korupsi - Rahmawati, Rahma Wati (Maliki Interdisciplinary Journal, 2025)
Corruption in Indonesia has evolved into a systemic issue deeply rooted in the nation’s social, political, and economic structures. This condition has triggered a crisis of legitimacy and public trust in governmental institutions. Generation Z, a digitally native demographic, exhibits unique sociopolitical responses distinct from previous generations. One of their most notable expressions is the viral hashtag #KaburAjaDulu (“Just Flee for Now”) circulating on social media platforms. Although it appears to be a form of escapism, this movement carries a strong symbolic meaning as a passive resistance against entrenched oligarchic power and institutionalized corruption.This article is a conceptual study aimed at analyzing #KaburAjaDulu as a symbol of passive resistance by Generation Z against systemic corruption. Using discourse analysis of digital content and theoretical frameworks on national identity (Anderson), institutional corruption (Rothstein), and digital nationalism, this paper formulates a conceptual model linking systemic corruption, the erosion of public trust, digital resistance, and the reimagination of national identity.The study finds that #KaburAjaDulu represents a transformation in how resistance is articulated from physical mobilization to symbolic digital activism while also marking the emergence of a new political consciousness among youth. This article offers a theoretical contribution to the understanding of national identity dynamics in the social media era and serves as a conceptual foundation for future research on youth resistance toward corrupt political systems.